2015
DOI: 10.1097/hco.0000000000000157
|View full text |Cite
|
Sign up to set email alerts
|

Women, the menopause, hormone replacement therapy and coronary heart disease

Abstract: Prescription of HRT should never be made only for cardiovascular risk reduction. However, when symptom-related and other indications are present, HRT is appropriate and well tolerated in the early years after menopause with onset at a normal age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 63 publications
3
15
0
Order By: Relevance
“…In the present study, there was no difference in HDL-chol and LDL-chol levels, whereas Total-C levels and body weight were observed to increase after ovariectomy. Increased Total-C level and body weight are consistent with the findings of previous work reporting atherosclerosis tendency at menopause 29. 17-β E2 is a natural human estrogen and compensates for the physiological estrogen deficiency without affecting liver function.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, there was no difference in HDL-chol and LDL-chol levels, whereas Total-C levels and body weight were observed to increase after ovariectomy. Increased Total-C level and body weight are consistent with the findings of previous work reporting atherosclerosis tendency at menopause 29. 17-β E2 is a natural human estrogen and compensates for the physiological estrogen deficiency without affecting liver function.…”
Section: Discussionsupporting
confidence: 91%
“…These effects clearly mimic those observed in human menopause (Barrett-Connor 2013). Thus, our data provide strong evidence in favor of estrogen substitution therapy (Al-Safi & Santoro 2014, Whayne & Mukherjee 2015.…”
Section: :2supporting
confidence: 56%
“…34 Furthermore; our results were consistent with the studies whose reported impairment of lipid metabolism in OVX animals 35 and human. 36 Total thiols, the most predominant non-protein thiol, are involved in many biological activities including neutralization of reactive oxygen species (ROS), detoxification of xenobiotics and maintenance of -SH level in proteins. 37 Depletion of total thiols pool severely compromised antioxidant capacity.…”
Section: Discussionmentioning
confidence: 99%